Respuesta :

Extraneous solution:

An extraneous solution is a solution that arises from the solving process that is not really a solution at all

So, firstly we will solve for the equation

and then we verify each solutions by plugging them back

If denominator of rational equation becomes zero , then that solution must be extraneuous solution

For example:

[tex]\frac{1}{x+3} +\frac{2}{x} =-\frac{3}{x(x+3)}[/tex]

we can solve for x

Multiply both sides by x(x+3)

[tex]\frac{1}{x+3}x\left(x+3\right)+\frac{2}{x}x\left(x+3\right)=-\frac{3}{x\left(x+3\right)}x\left(x+3\right)[/tex]

now, we can simplify it

[tex]x+2\left(x+3\right)=-3[/tex]

[tex]x+2x+6=-3[/tex]

[tex]3x=-9[/tex]

now, we can solve for x

[tex]x=-3[/tex]

now, we can check whether x=-3 is extraneous solution

we will plug back x=-3 into original

[tex]\frac{1}{-3+3} +\frac{2}{-3} =-\frac{3}{-3(-3+3)}[/tex]

[tex]\frac{1}{0} +\frac{2}{-3} =-\frac{3}{-3(0)}[/tex]

we can see that denominator becomes 0

so, x=-3 can not be solution

so, x=-3 is extraneous solution...........Answer

Answer:

If a solution results in zero when substituted into the denominator of the equation, the solution is extraneous.